Companion or Stray? Conflicting Beliefs of Veterinary Professionals and Animal Help Volunteers in Latvia - Šeiko, Staņislavs; Možarova, Aleksandra (Italian Sociological Review, 2025)
In Latvia veterinarians, veterinary inspectors, and homeless animal help volunteers are the main social groups involved in animal rights protection. They frequently engage with companion or stray animals, and their beliefs regarding the moral value of animals and comprehension of animal rights may affect their perspectives on the topic of pets and strays. Prior research has revealed the existing contradictions between veterinary professionals and homeless animal help volunteers in Latvia. This study investigates the possible causes of these contradictions by analysing informants’ beliefs regarding the moral status, value, and legal rights of companion animals and stray animals. The animal is used as an explanatory instrument in this study, conducted from 2022 to 2024 and utilizing a qualitative methodology. 30 semi-structured interviews offer a refined comprehension of the distinctions between veterinary professionals and volunteers. The beliefs of volunteers are frequently shaped by emotional ties to animals, resulting in a moral advocacy for their rights. In contrast, veterinary professionals ground their beliefs in the Five Freedoms framework and practical considerations of animal welfare, which may conflict with the emotional motivations of volunteers. Conflicting perspectives on legal rights result in varied interpretations of ethical treatment and care for animals. Also, diversities in beliefs significantly influence the management of stray animal populations, potentially resulting in conflict or ineffective policy outcomes if not properly handled, as well as affecting the legislative reforms aimed at improving the welfare of domestic and stray animals.